Perinatal outcomes in a hospital from southern Brazil: Predictors of low APGAR in the first minute of birth - Wolf, Jonas Michel (Clinical and Biomedical Research, 2024)
Introduction: The Apgar Index (AI), is a method that assesses the physical conditions of the newborn (NB) in the period immediately after birth. The index proved to be a predictor of neonatal mortality in several clinical and population-based studies and has been used as a health assessment parameter in the immediate neonatal period for over 60 years. Objective: To evaluate obstetric history and perinatal outcomes in newborns (NB) Apgar score equal zero in the first minute of life. Data from births in a public hospital in southern Brazil were evaluated. The studied population was divided into two groups: cases (AI equal zero) and controls (NB with AI ≥8). The cases were composed of 219 NB and the controls of 657 NB. Results: In the multivariate analysis, the maternal variables predictors of AI zero in the first minute of life were: mother’s age >25 years [odds ratio (OR): 1.8; confidence interval (95%CI): 1.1 – 2.8; p = 0.020] and absence of prenatal care (OR: 2.8; 95%CI: 1.5 – 5.5; p = 0.010). Death in the delivery room was higher in cases compared to controls (p < 0.001). Additionally, predictive neonatal variables were: umbilical arterial pH (<7.0) (OR: 5.2; 95%CI: 4.0 – 8.8; p <0.001), base excess (>-6.5) (OR: 4.1; 95%CI: 3.3 – 10.5; p <0.001), fetal breech presentation (OR: 7.1; 95%CI: 4.2 – 13.1; p <0.001), gestational age <33 weeks (OR: 15.1; 95%CI: 5.8 – 20.3; p <0.001), fetal weight <2500g (OR: 21.5; 95%CI: 12.1 – 31.9; p <0.001) and hemorrhagic amniotic fluid (OR: 13.8; 95%CI: 5.4 – 48.6; p <0.001). Conclusion: Absence of prenatal care, maternal age, low birth weight, prematurity, breech presentation, hemorrhagic amniotic fluid, low AI in the fifth minute of life, lower umbilical artery pH values, and higher base excess values are related to AI zero in the first minute.